Optimizing Project Implementation Time and Cost Using the Least Cost Method - Astariani, Ni Kadek; Pagehgiri, Juniada; Pratama, Naris (ASTONJADRO, 2025)
The background of this study is project delays. In the implementation of a project, projects are often found to be delayed or the implementation of the project is not in accordance with the predetermined schedule. Optimize the time and cost of implementing a late project using the least cost analysis method. The Least Cost Analysis method is a method for accelerating work to obtain optimal project duration in a project by carrying out work activities simultaneously in the implementation of the project which can help complete a project efficiently and effectively. The SP. Buruan - Senganan - Pacung Provincial Road Construction Project is used as a case study which experienced a 10,61% delay in work progress in the 28th week. The application of the Least Cost Analysis method is only on work activities that are on the critical path in order to restore the project completion schedule to be completed according to schedule to avoid progress delays. The results of the application of the Least Cost Analysis method optimize the time and cost of completing the project on time, namely the time efficiency of 10,61% from the late time. In terms of cost, a cost efficiency of Rp. 328.135.246,76 or 2,52% is obtained.